Proceedings of the 3rd International Conference on Accounting, Management and Economics 2018 (ICAME 2018) 2019
DOI: 10.2991/icame-18.2019.17
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of XBRL Adoption on the Investors’ Trading Behavior in Indonesia Stock Exchange

Abstract: This research aimed to examine the effect of XBRL (Extensible Business Reporting Language) adoption on investors' trading behavior in Indonesia Stock Exchange which was reflected in the frequency of trading on Indonesia Stock Exchange. By using a number of 34 banking issuers taken randomly from a number of 81 banking issuers listed in the Indonesia Stock Exchange in 2014 and 2016, and using one way ANOVA analysis method, for t-test, to see the effect of pre and post XBRL adoption on trading shares frequencies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…The results show that Hypothesis 2 can be accepted, but with a negative effect that is contrary to the existing theory. The results of this study are not in line with Razak's (2019) research indicating that size affects the XBRL response, meaning that small companies respond to the existence of XBRL. Masrifa's research (2016) shows a significant effect on firm value, that the greater the size of the company, the faster the turnover of assets (the more effective the company is in generating profits from the use of its assets) and a positive signal for investors that the better the company's performance will increase investors' interest in investing, and in the end, the value of the company will increase.…”
Section: Firm Size Is Significantly and Positively Related To Value R...contrasting
confidence: 99%
See 2 more Smart Citations
“…The results show that Hypothesis 2 can be accepted, but with a negative effect that is contrary to the existing theory. The results of this study are not in line with Razak's (2019) research indicating that size affects the XBRL response, meaning that small companies respond to the existence of XBRL. Masrifa's research (2016) shows a significant effect on firm value, that the greater the size of the company, the faster the turnover of assets (the more effective the company is in generating profits from the use of its assets) and a positive signal for investors that the better the company's performance will increase investors' interest in investing, and in the end, the value of the company will increase.…”
Section: Firm Size Is Significantly and Positively Related To Value R...contrasting
confidence: 99%
“…Muchlis (2019) shows that XBRL does not make financial reports more informative. Meanwhile, Razak (2019) found that the frequency of stock trading and ROA as control variables did not change when XBRL was implemented, while the implementation of XBRL was only carried out in 2015. However, size and dividends changed during the post-XBRL period.…”
Section: Corporate Governancementioning
confidence: 99%
See 1 more Smart Citation